A qualitative summative assessment for theater education. Issue 3 (3rd July 2019) - Tabone, Carmine; Weltsek, Gustave J.
Abstract: This article reviews the development of a qualitative summative assessment based on the National Theater Standards to evaluate theater education classes. The authors examine the current state of the field of theater education; the use of the assessment; an overview of the results of an arts integration U.S. Department of Education project; and a look at some of the student work. Finally, the article considers some of the complications and challenges that can arise from this type of process.